UNEMPLOYMENT, POVERTY AND INDONESIAN OVERSEAS WORKERS - Djafar, Fariastuti; Kurniasih, Erni Panca (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
Indonesia faces unemployment and poverty problems which may cause this country as one of the main countries in Asia to send international migrant workers. The main objective of this paper is to examine whether unemployment and poverty determine Indonesian Overseas Workers (IOWs). The study uses secondary data and the data are analysed by utilizing a Vector Autoregressive (VAR) framework. The findings show that unemployment has a significant negative effect on the IOWs while poverty has a significant positive effect. The unemployed youth in Indonesia mainly have higher education and are not poor which are least likely to migrate while poor people migrate for survival. Hence, freeze on sending the IOWs may not be effective since the poor people will keep working overseas by being illegalworkers.